Method for forming stable hydrophobic surface on steel workpiece

Through the method of rough treatment and sedimentary hydrophobic layer on the steel workpiece, the problem of unstable hydrophobicity of steel workpieces in existing technologies has been solved, and highly abrasion -resistant and long -term durability hydrophobic surfaces have been achieved. Economy and environmental.

CN119372590APending Publication Date: 2025-01-28NANO & ADVANCED MATERIALS INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411018879.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2024-07-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to form a highly wear-resistant hydrophobic surface on steel workpieces for a long time and stable, and the traditional methods are not economical and environmentally friendly.

Method used

The concave part of the surface of the steel workpiece is treated by rough treatment, and then the hydrophobic layer is deposited into the concave part. Micro-/nano-grade roughness is formed by sandblasting, electric polishing and etching. The hydrophobic layer containing fluoride polymer or silicon/epoxy resin hybrid polymer.

Benefits of technology

The formation of a stable and hydrophobic surface is achieved on steel workpieces, with good abrasion resistance and long -term durability, and high stability in the wear and flushing test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372590A_ABST
    Figure CN119372590A_ABST
Patent Text Reader

Abstract

The invention discloses a method for forming a stable hydrophobic surface on a steel workpiece, which comprises the following steps of: firstly, roughening the steel workpiece by removing part of the steel from the surface so as to form a concave part; and secondly, a hydrophobic layer is deposited into the concave part, so that the steel workpiece with a stable hydrophobic surface is formed, and good wear resistance is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a material surface modification, and in particular to a method for improving the long-term durability of a hydrophobic surface of a steel material and forming a stable hydrophobic surface on a steel workpiece. Background Art

[0002] Superhydrophobic surfaces have recently attracted great attention due to their special functions such as self-cleaning, anti-corrosion, anti-icing, drag reduction and antibacterial. Surfaces with a water contact angle greater than 150° are usually classified as superhydrophobic surfaces. Many organisms in nature, including lotus leaves, rice leaves, butterfly wings and water strider legs, show excellent superhydrophobicity.

[0003] Generally speaking, the formation of superhydrophobic surfaces involves two key methods: constructing a rough surface with micron / nanoscale roughness, and performing surface modification to reduce the surface free energy. Existing technologies have provided many methods for preparing superhydrophilic surfaces, such as electrochemical deposition, plasma method, chemical vapor deposition, wet chemical reaction, hydrothermal method, etc. Many surfaces manufactured by chemical methods have good superhydrophobicity, but the stability and service life are low. On the other hand, these methods usually cannot meet today's industrial requirements because they are economically unfeasible or because they cause serious environmental pollution. Summary of the invention

[0004] The present invention provides a method for forming a stable hydrophobic surface on a steel workpiece. First, a concave portion is formed by roughening the surface of the steel workpiece; second, a hydrophobic layer is deposited into the concave portion, thereby forming a steel workpiece with a stable hydrophobic surface and exhibiting good wear resistance.

[0005] In one embodiment of the present invention, the roughening process further comprises:

[0006] Shot blasting of steel workpieces, wherein the sand blasting uses a stream of air mixed with inorganic particles to create a micron / nanometer surface roughness;

[0007] Electropolishing the blasted steel workpiece, wherein the blasted steel workpiece serves as an anode; and

[0008] The electropolished steel workpiece is subjected to an etching process, wherein the etching process uses an etching solution containing ferric chloride.

[0009] In another embodiment of the present invention, the deposition process comprises physical vapor deposition (PVD). Preferably, the hydrophobic layer comprises a fluoropolymer, and the steel workpiece after deposition has a water contact angle of at least 110 degrees after 1000 wear tests.

[0010] In yet another embodiment of the present invention, the deposition process comprises a sol-gel process. Preferably, the hydrophobic layer comprises a silica / epoxy hybrid polymer, and the steel workpiece after deposition has a water contact angle of at least 110 degrees after 1000 wear tests.

[0011] The above description is only a summary of the technical solution of the present invention. A complete embodiment of the present invention is provided below in conjunction with the accompanying drawings to make it easier for those skilled in the art to understand the operation process and its objectives, features and advantages of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The present invention may be fully understood by reading the following detailed description of complete embodiments with reference to the accompanying drawings, in which:

[0013] Figure 1 3D white light interferometry images of the pretreated sample surfaces, after step 1 - sandblasting, step 2 - electropolishing, and step 3 - etching.

[0014] Figure 2A Shown are water contact angle values ​​for PVD and sol-gel samples after 200, 500, and 1000 abrasion cycles.

[0015] Figure 2B Shown are water contact angle values ​​for detergent and ethanol rinse tests for PVD and sol-gel samples. DETAILED DESCRIPTION

[0016] In this application, when an element or component is referred to as being included in and / or selected from a list of listed elements or components, it should be understood that the element or component can be any of the listed elements or components, or the element or component can be selected from a group consisting of two or more of the listed elements or components. In addition, it should be understood that the elements, compound group characteristics, equipment devices or methods described herein will be combined in a variety of ways, whether explicitly or implicitly herein, without departing from the spirit and scope of the present guidance.

[0017] Use of the terms "including," "comprising," "having," or "having" are generally accepted to be open ended and non-limiting unless expressly stated otherwise.

[0018] When the singular is used herein, the plural is also included (and vice versa), unless otherwise expressly stated. In addition, when the term "about" is used before a quantitative value, the specific quantitative value itself is also included in this patent, unless otherwise expressly stated. When the term "about" is used herein, it means within a range of ±10% from the standard value, unless otherwise stated or inferred.

[0019] The order of the steps and the execution of an operation procedure is not critical, as long as the guidelines in the patent remain valid. In addition, two or more actions can be performed simultaneously.

[0020] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0021] The present invention can be applied to various types of steel surfaces, such as carbon steel, high-speed steel, pearlite steel, austenite steel and stainless steel. Stainless steel is well known for its good corrosion resistance and excellent mechanical properties and has been widely used in fields such as heat exchange, food, power generation and petrochemical industries. However, due to the high wettability of the stainless steel surface, there are still some defects, which lead to easy adhesion of liquid or corrosion in a high humidity environment. The self-cleaning, corrosion resistance and antifouling properties of super-hydrophobic surfaces can effectively solve these problems. Therefore, surface modification of stainless steel to create a super-hydrophobic surface has attracted widespread attention.

[0022] The hydrophobicity of a coating depends on its surface chemistry and morphology. Generally speaking, a hydrophobic coating has a low surface energy, resulting in a water-repellent surface. A coating with a low surface energy will tend to repel water. This is because water molecules are more strongly attracted to each other than to the surface, resulting in a contact angle greater than 90 degrees. Therefore, first, low surface energy coatings with hydrophobic groups, such as fluorine groups, will be developed by PVD or sol-gel methods.

[0023] Secondly, a rough surface makes it difficult for water to wet the surface, resulting in hydrophobicity. This is because roughness creates air pockets on the solid surface, which prevents water droplets from spreading. Therefore, increasing the surface roughness is the most important thing we want to achieve in the pretreatment step. In summary, combining the coating method and roughening is our strategy for preparing hydrophobic or super-hydrophobic coatings on steel surfaces.

[0024] The present invention provides a method for forming a stable hydrophobic surface on a steel workpiece, comprising:

[0025] (1) Roughening process: roughening the steel workpiece by removing portions of the steel from the surface, thereby forming recesses; and

[0026] (2) Deposition process: A hydrophobic layer is deposited into the recesses, thereby forming a steel workpiece with a stable hydrophobic surface, exhibiting good wear resistance.

[0027] In one embodiment of the present invention, the roughening process further comprises:

[0028] Shot blasting of steel workpieces, wherein the sand blasting uses a stream of air mixed with inorganic particles to create a micron / nanometer surface roughness;

[0029] Electropolishing the blasted steel workpiece, wherein the blasted steel workpiece serves as an anode; and

[0030] The electropolished steel workpiece is subjected to an etching process, wherein the etching process uses an etching solution containing ferric chloride.

[0031] In this embodiment, the sandblasting treatment is performed by blowing an air flow mixed with inorganic particles at a pressure of 2 to 5 bars. The air flow is blown in from a distance of about 8 to 12 cm from the steel workpiece being treated. The size of the inorganic particles is 10 to 40 microns. The surface roughness (Ra) of the steel workpiece after sandblasting is greater than 600 nanometers.

[0032] The electropolishing process uses an electrolyte comprising 50 to 70 weight percent of concentrated phosphoric acid, 20 to 40 weight percent of concentrated sulfuric acid, polyethylene glycol, hexamethylenetetramine, citric acid, thiourea, glycerol and water. The electropolishing process uses a constant voltage of 3 to 8V, and the electropolishing time is about 40 to 100 seconds.

[0033] The etching solution of the etching treatment comprises (1) ferric chloride with a volume molar concentration of 1 to 2 M, (2) at least one acid selected from the group consisting of hydrochloric acid and phosphoric acid and mixtures thereof, (3) hydrogen peroxide with a volume molar concentration of 1 to 2 M, and (4) water. Preferably, the volume molar concentration of the acid in the etching solution is 1 to 3 M. The etching treatment requires cooling by a water bath, and the water bath temperature is between 40 and 60 degrees Celsius. The etching treatment time is about 40 to 80 minutes, and the surface of the steel workpiece after etching is similar to the surface of a lotus leaf.

[0034] In a preferred embodiment of the present invention, after the roughening process, a cleaning process is required to remove chemical residues and byproducts from the roughened steel workpiece.

[0035] In another embodiment of the present invention, the deposition process includes physical vapor deposition (PVD). The deposition process uses a PVD device having a vacuum processing chamber in which a DC magnetron sputtering cathode is disposed, and the device is configured to perform physical vapor deposition on an etched steel workpiece in the chamber when a sputtering power level of 50-100W is applied to the sputtering cathode, wherein the process gas is maintained at a vacuum processing pressure level of 1-5 Pascals (Pa). The temperature range of the chamber is 20 to 40 degrees Celsius. The sputtering process time is about 30 to 90 minutes.

[0036] The hydrophobic layer formed by PVD includes a fluorine-containing polymer or an inorganic fluorine-containing compound. Preferably, the hydrophobic layer includes perfluoroalkoxy (PFA), and the steel workpiece after PVD deposition has a water contact angle of at least 110 degrees after 1000 wear tests. On the other hand, the steel workpiece after PVD deposition has a water contact angle loss of less than 10 degrees after ethanol and detergent rinsing tests.

[0037] In yet another embodiment of the present invention, the deposition process comprises a sol-gel process, which comprises:

[0038] providing a sol-gel solution;

[0039] applying the sol-gel solution into a recess of a steel workpiece; and

[0040] The sol-gel solution in the recessed portion is cured to form a hydrophobic layer comprising a silica / epoxy hybrid polymer.

[0041] The sol-gel solution comprises 20 to 30 weight percent of epoxy resin (E-51), ethanol, 12 to 22 weight percent of tetraethyl orthosilicate (TEOS) and 35 to 45 weight percent of 3-aminopropyltriethoxysilane (APTES). The curing temperature range is 50 to 90 degrees Celsius. Preferably, the sol-gel hydrophobic layer comprises a silica / epoxy hybrid polymer, and the steel workpiece after sol-gel deposition has a water contact angle of at least 110 degrees after 1000 wear tests. On the other hand, the steel workpiece after sol-gel deposition has a water contact angle loss of less than 10 degrees after ethanol and detergent rinse tests.

[0042] First embodiment - Roughening procedure

[0043] Material

[0044] The stainless steel plates with the size of 25mm*75mm*1mm were strictly cleaned before subsequent use, including ultrasonic cleaning with acetone for 10 minutes, ultrasonic cleaning with alcohol for 10 minutes, and ultrasonic cleaning with distilled water for 10 minutes. After cleaning, all samples were dried in a thermostat at 70 degrees Celsius.

[0045] Pre-treatment step 1: Sandblasting

[0046] Sandblasting is an operation in which a stream of abrasive is pressed against a surface under high pressure to smooth a rough surface, roughen a smooth surface, engrave a surface, or remove surface contaminants. In detail, aluminum oxide (Al2O3) with a particle size of 25 μm was used as an abrasive to sandblast the above-prepared sample. During the sandblasting process, the nozzle was kept at a consistent distance of 10 cm from the sample surface. The process requires manual scanning line by line, keeping the surface as flat as possible during the entire process. After sandblasting, the surface roughness is expected to increase dramatically.

[0047] Pre-treatment step 2: Electropolishing

[0048] Electropolishing is an electrochemical finishing process that removes a thin layer of surface material from a metal component. The process results in a smoother, cleaner surface.

[0049] The electrolyte used for stainless steel usually consists of a high-viscosity mixture of sulfuric acid and phosphoric acid. Specifically, before starting to prepare the electrolyte, sufficient ice cubes and ice water should be prepared to cool the acid during the mixing process to avoid accidents caused by the concentrated acid boiling or splashing out of the container. First, weigh 765 ml of concentrated phosphoric acid with a concentration of 85% and slowly pour it into a glass container of appropriate size. Secondly, weigh 435 ml of concentrated sulfuric acid with a concentration of 95%, slowly pour it into the concentrated phosphoric acid, and stir it with a glass rod or magnet while pouring. This process needs to be carried out in an ice bath, and ice water and ice cubes are used to cool the outside of the container in time to avoid accidents. Third, when the acid is mixed evenly and the temperature drops to room temperature, add 8.3424 grams of polyethylene glycol 6000, 2.0856 grams of hexamethylenetetramine, 10.428 grams of citric acid, 0.20856 grams of thiourea, 12 milliliters of glycerol and 48 milliliters of water, stir thoroughly to mix the solution evenly, and finally obtain a clear and transparent electrolyte. Finally, the electrolyte can be stored in a glass container.

[0050] During the electropolishing process, the metal part acts as a positively charged anode. The stainless steel plate treated in step 1 is connected to the positive terminal of a DC power rectifier. A negatively charged cathode, usually made of zirconium, is connected to the negative terminal of the DC power rectifier. Both the anode and cathode are immersed in a temperature-controlled bath of the electrolyte solution prepared above. In step 2, the temperature of each stainless steel plate is maintained below 70 degrees Celsius and the power supply is maintained at 5V for 40 seconds.

[0051] Micro-smoothness can be improved with electropolishing. It flattens peaks and valleys and improves surface roughness. Unlike mechanical finishing, electropolishing removes surface imperfections without staining, bending, breaking or stressing crystalline metals. Electropolishing also removes tiny surface particles that can get stuck and break at a microscopic level.

[0052] Pre-processing step 3: Etching

[0053] A chemical etchant is prepared in the following proportions, containing 16 g of iron (III) chloride, 60 ml of distilled water, 2 ml of hydrochloric acid-hydrogen chloride, 2 ml of phosphoric acid, and 2 ml of hydrogen peroxide. A magnetic stirrer is used to stir the solution until it is homogeneous. The prepared chemical etchant can be stored in a glass container.

[0054] During the etching process, first, the stainless steel plate treated in step 2 was immersed in the prepared chemical etchant and kept in a water bath at 50 degrees Celsius for 60 minutes. After the etching process, iron easily reacts with hydrochloric acid and ferric chloride to corrode the stainless steel surface, forming a microstructure similar to the surface of a lotus leaf. Then, the treated stainless steel plates were strictly cleaned to remove the etchant, including 10 minutes of ultrasonic cleaning with acetone, 10 minutes of ultrasonic cleaning with alcohol, and 10 minutes of ultrasonic cleaning with distilled water. After cleaning, all stainless steel plates were dried in a thermostat at 70 degrees Celsius.

[0055] Figure 1 The 3D white light interferometer graph of the sample surface after each step is shown. The average roughness Ra of the sample surface after sandblasting, electropolishing and etching is 670.83, 617.45 and 454.87 nm, respectively. The sandblasting process significantly increases the surface roughness. Then, the electropolishing process removes burrs and surface defects, making the surface of the stainless steel sample smoother at the microscopic level. The etching process forms a microstructure similar to the lotus leaf surface on the surface of the stainless steel plate.

[0056] Second embodiment - Combining roughening process with physical vapor deposition (PVD)

[0057] Perfluoroalkoxy (PFA) is a copolymer of a small amount of perfluoropropyl perfluoroacetaldehyde and polytetrafluoroethylene acetone. Due to the inherent properties of PFA and the properties of the fluorine groups in PFA, the surface of the PFA coating is expected to have a low friction coefficient and be hydrophobic and oleophobic.

[0058] PFA coating can be synthesized by a variety of methods, including laser irradiation, spraying and other methods. In the present invention, PFA coating is directly deposited by radio frequency (RF) magnetron sputtering using a PFA target (99.9% purity). In detail, the stainless steel plate pretreated in the first embodiment is placed in the chamber and heated to at least 10 -4 The base ambient pressure level was 1 Pa. The pressure was then increased to 1 Pa under Ar atmosphere and the flow rate was maintained at 20 sccm throughout the sputtering process. The sputtering power was kept below 100 W at a fixed 100 W RF power.

[0059] After PVD coating, the stainless steel plate showed hydrophobic properties, such as Figure 2A and Figure 2B As shown in Figure 2, the stainless steel plate with PFA PVD coating can achieve an average water contact angle of 150 degrees. The wear test and flushing test are used to test the stability of the hydrophobicity of the stainless steel sample.

[0060] like Figure 2AAs shown in the figure, the water contact angle was measured after 200, 500 and 1000 abrasions. After 1000 abrasions, the PVD coated sample can still maintain 112.65 degrees. After 1000 abrasion tests, the contact angle of the coating surface is not less than 110 degrees. Figure 2B As shown, the water contact angle was tested after 5 minutes of detergent rinsing, 5 minutes of detergent ultrasonic rinsing, and 5 minutes of ethanol ultrasonic rinsing. After the above 15 minutes of rinsing, the PVD coated sample can still maintain 144.73 degrees. After the rinsing test, the coating will not peel off.

[0061] Third Example - Combining Roughening Process and Sol-Gel (SG) Deposition

[0062] In a round-bottom flask, a mixture of epoxy resin (E-51), ethanol, tetraethyl orthosilicate (TEOS) and 3-aminopropyltriethoxysilane (APTES) in a weight ratio of 26%:17%:17%:40% was prepared into a sol-gel solution in the following proportions. Initially, E-51, ethanol and TEOS were mixed to obtain a white turbid mixture. After stirring for 10 minutes, APTES was added, causing the mixture to suddenly become transparent. The resulting organic-inorganic hybrid epoxy resin-based adhesive was continuously stirred at room temperature for 4 hours. The synthesized adhesive was transparent and could be stored at room temperature for at least 6 months without any changes.

[0063] During the sol-gel spraying process, the sol-gel solution is sprayed onto the surface of the stainless steel plate pretreated in the first embodiment. During the sol-gel spraying process, the nozzle is kept at a consistent distance of 10 cm from the sample surface. The process requires manual scanning line by line, and the surface is kept as flat as possible during the entire process. Then, it is cured at a temperature of 80 degrees Celsius for 1 hour to make the coating more robust. After the sol-gel spraying process, the surface hydrophobicity is expected to be significantly improved.

[0064] After sol-gel coating, the stainless steel plate showed hydrophobic properties, e.g. Figure 2A and Figure 2B As shown in the figure, the average water contact angle of the stainless steel plate using sol-gel spraying technology can reach 165.3 degrees. The following wear test and flushing test are used to test the stability of the hydrophobicity of the stainless steel sample.

[0065] like Figure 2A As shown in the figure, the water contact angle was measured after 200, 500 and 1000 abrasions. After 1000 abrasions, the sample of the sol-gel coating can still maintain 115.58 degrees. After 1000 abrasion tests, the contact angle of the coating surface is not less than 110 degrees. Figure 2BAs shown, the water contact angle was tested after 5 minutes of detergent rinsing, 5 minutes of detergent ultrasonic rinsing, and 5 minutes of ethanol ultrasonic rinsing. After the above 15 minutes of rinsing, the sample of the sol-gel coating can still maintain 151.13 degrees. After the rinsing test, the coating will not peel off.

[0066] In summary, combining the roughening process with physical vapor deposition (PVD) or combining the roughening process with sol-gel deposition can produce a stable hydrophobic coating.

[0067] The above embodiments are only used to illustrate the principle of the present invention and should not be construed as any limitation to the present invention. The above embodiments can be modified by a person skilled in the art without departing from the scope of the present invention as defined in the following claims.

Claims

1. A method for forming a stable hydrophobic surface on a steel workpiece, characterized in that: include: (1) Roughening process: Roughening the steel workpiece by removing part of the steel from the surface, thereby forming a concave portion; as well as (2) Deposition process: A hydrophobic layer is deposited into the recesses, thereby forming a steel workpiece with a stable hydrophobic surface, exhibiting good wear resistance.

2. The method according to claim 1, characterized in that The roughening procedure further comprises: Shot blasting of steel workpieces, wherein the sand blasting uses a stream of air mixed with inorganic particles to create a micron / nanometer surface roughness; Electropolishing the blasted steel workpiece, wherein the blasted steel workpiece serves as an anode; and The electropolished steel workpiece is subjected to an etching process, wherein the etching process uses an etching solution containing ferric chloride.

3. The method according to claim 2, characterized in that The size of the sandblasted inorganic particles is 10 to 40 microns.

4. The method according to claim 2, characterized in that The sandblasting process involves blowing in a stream of air mixed with inorganic particles at a pressure of 2 to 5 bar.

5. The method according to claim 2, characterized in that The surface roughness of the steel workpiece after sandblasting is greater than 600 nanometers.

6. The method according to claim 2, characterized in that The electropolishing process uses an electrolyte comprising 50 to 70 weight percent of concentrated phosphoric acid, 20 to 40 weight percent of concentrated sulfuric acid, polyethylene glycol, hexamethylenetetramine, citric acid, thiourea, glycerin and water.

7. The method according to claim 2, characterized in that The electropolishing process uses a constant voltage of 3 to 8V.

8. The method according to claim 2, characterized in that The etching solution for the etching treatment comprises: ferric chloride with a volume molar concentration of 1 to 2 M, at least one acid selected from the group consisting of hydrochloric acid, phosphoric acid and a mixture thereof, hydrogen peroxide with a volume molar concentration of 1 to 2 M, and water.

9. The method according to claim 8, characterized in that The acid volume molar concentration in the etching solution is 1 to 3M.

10. The method according to claim 2, characterized in that The etching process is cooled by a water bath having a temperature between 40 and 60 degrees Celsius.

11. The method according to claim 2, characterized in that The surface of the etched steel workpiece is similar to the surface of a lotus leaf.

12. The method according to claim 1, characterized in that After the roughening process, a cleaning process is performed to remove chemical residues and by-products from the roughened steel workpiece.

13. The method according to claim 1, characterized in that The deposition process includes physical vapor deposition.

14. The method according to claim 13, characterized in that The deposition procedure uses a PVD device having a vacuum processing chamber in which a DC magnetron sputtering cathode is configured, and the device is configured to perform physical vapor deposition on an etched steel workpiece in the chamber when a sputtering power level of 50-100 W is applied to the sputtering cathode, wherein the process gas is maintained at a vacuum process pressure level of 1-5 Pa.

15. The method according to claim 14, characterized in that The temperature of the chamber ranges from 20 to 40 degrees Celsius.

16. The method according to claim 1, wherein: The hydrophobic layer includes a fluorine-containing polymer or an inorganic fluorine-containing compound.

17. The method according to claim 16, characterized in that The hydrophobic layer includes a perfluoroalkoxy group.

18. The method according to claim 13, characterized in that Steel workpieces with a stable hydrophobic surface include one, any combination, or all of the following characteristics: The average water contact angle is equal to or greater than 150 degrees; A water contact angle of at least 110 degrees after 1,000 abrasion cycles; and After ethanol and detergent rinsing tests, the water contact angle loss was less than 10 degrees.

19. The method of claim 1, wherein: The deposition process includes a sol-gel process.

20. The method of claim 19, wherein: The sol-gel procedure includes: providing a sol-gel solution; applying the sol-gel solution into a recess of a steel workpiece; and The sol-gel solution in the recessed portion is cured to form a hydrophobic layer comprising a silica / epoxy hybrid polymer.

21. The method of claim 20, wherein: The sol-gel solution contains 20 to 30 weight percent of epoxy resin, ethanol, 12 to 22 weight percent of tetraethyl orthosilicate, and 35 to 45 weight percent of 3-aminopropyltriethoxysilane.

22. The method of claim 20, wherein: The curing temperature ranges from 50 to 90 degrees Celsius.

23. The method of claim 19, wherein: Steel workpieces with a stable hydrophobic surface include one, any combination, or all of the following characteristics: The average water contact angle is equal to or greater than 150 degrees; A water contact angle of at least 110 degrees after 1,000 abrasion cycles; and After ethanol and detergent rinsing tests, the water contact angle loss was less than 10 degrees.